2016
DOI: 10.1007/s11157-016-9399-5
|View full text |Cite
|
Sign up to set email alerts
|

Membrane bioreactor technology for leachate treatment at solid waste landfills

Abstract: Controlled landfilling remains a commonly applied method for municipal solid waste disposal with leachate generation being an inevitable consequence of the decomposition of the waste and the percolation of water through decomposing waste. The membrane bioreactor (MBR) technology has evolved into an effective process in treating such high strength wastewater streams because of its ability to retain high biomass concentration through membrane separation. This paper presents a critical review of the application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 145 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…Membrane bioreactors, which combine microfiltration or ultrafiltration membranes with biological reactors, have gained popularity in recent years and are regarded as advanced treatment processes due to their high effluent quality and flexibility [112]. Studies on treatment processes have shown that membrane bioreactors outperform traditional biological treatment systems across various loading circumstances, particularly when treating leachate from old landfills [113]. However, applying high-loading circumstances, extended hydraulic retention time and solids retention time, and high concentrations of pollutants can promote membrane fouling.…”
Section: Membrane Separation-admentioning
confidence: 99%
“…Membrane bioreactors, which combine microfiltration or ultrafiltration membranes with biological reactors, have gained popularity in recent years and are regarded as advanced treatment processes due to their high effluent quality and flexibility [112]. Studies on treatment processes have shown that membrane bioreactors outperform traditional biological treatment systems across various loading circumstances, particularly when treating leachate from old landfills [113]. However, applying high-loading circumstances, extended hydraulic retention time and solids retention time, and high concentrations of pollutants can promote membrane fouling.…”
Section: Membrane Separation-admentioning
confidence: 99%
“…Predictions indicate that there will be a trend over the next 20 years to increase bio-wastes production and their occurrence in landfilling sites [101]. Leachate generation is considered a consequence of the bio-wastes decomposition in the landfills [102].…”
Section: Bio-wastes Mitigationmentioning
confidence: 99%
“…sludge (Campos et al, 2019), and membrane bioreactor treatment are effective processes in the treatment of high-strength wastewater (Hashisho and El-Fadel, 2016;Tałałaj et al, 2019).…”
Section: Ammoniacal Nitrogen (Nhmentioning
confidence: 99%